Hubungan Tingkat Pengetahuan dan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Penderita Tuberkulosis di Wilayah Kerja Puskesmas Pahandut: Correlation of Knowledge Levels and Family Support About Medication Adherence in Tuberculosis Sufferers in the Working Area of Pukesmas Pahandut - Lilis Andriani; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Tuberculosis was still a health problem for Indonesian and internationally, so it was one of the sustainable health development goals (SDGs), the success of TB treatment was influenced by the level of knowledge, family support and compliance of patients taking drugs, but in fact, because the long treatment period makes patients become saturated this was a factor that causes patients to not comply with taking drugs. The purpose of this research was to find out the relationship between the level of knowledge and family support with adherence to taking medications in tuberculosis sufferers. The research design was quantitative research with a cross-sectional approach, the research sample was all tuberculosis sufferers as many as 35 people who were in the work area of Pukesmas Pahandut, the statistical test used was a chi-square test with the help of a computer. Based on this research result, it may be concluded that had a good level of knowledge as many as 30 respondents (85.7%) had good family support as many as 28 respondents (80%) and obediently took drugs as many as 28 respondents (80%), there was a relationship between the level of knowledge and family support with adherence to taking drugs in tuberculosis sufferers with a pvalue value = 0.000 (α<0.05). Therefore, it was important for sufferers to increase their knowledge about tuberculosis and it will be better if the family provides support to the sufferer so that the patient was more motivated to recover and obey in taking drugs during the tuberculosis treatment period.